Implementasi Strategi Pembelajaran Model Stalking Stick Terhadap Motivasi Belajar Peserta Didik - Andrian; Siti Tiara Maulia (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
The Talking Stick learning method is a learning method that uses a stick that is not too long, the stick is rotated by all students while singing a song. The Talking Stick learning method is a very fun and tense learning method for students because they have to be ready and suddenly answer questions from the teacher. This research uses qualitative research using the results of descriptive from the results of collecting data from literature studies by reading and analyzing several theories which are reviewed in the form of journals, articles and books, the talking stick learning model is seen as a learning model that is able to increase students' learning motivation.